1987
DOI: 10.1007/bf00215417
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin-immunoreactive cells of peculiar shape in the urethral epithelium of the human penis

Abstract: The present study deals with endocrine-like cells in the urethra of human penis. A large number of basal-granulated cells immunoreactive for serotonin were dispersed in the urethral epithelium. No cellular elements were stained positively with antisera against bioactive peptides. The serotonin-immunoreactive cells consisted of a small oval perikaryon and slender processes, and resembled neurons in shape. An apical process reached the urethral lumen. The basal processes frequently branched out in a dendritic fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

1987
1987
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…On the other hand, Lendon et al (1976) claimed that, in humans, no serotonin-fluorescent cells occurred distal to the point of the entry of the ejaculatory ducts in the male or in the distal one-third of the female urethra. Our previous immunohistochemical study (Iwanaga et al, 1987) recognized numerous serotonin cells dispersed in the human penile urethra. Forsberg et al (1964) demonstrated serotonin-fluorescent cells in the vestibular and lower vaginal epithelia of rabbits, whereas no studies seem available concerning the paraneurons in the vestibule and vagina in other mammals.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…On the other hand, Lendon et al (1976) claimed that, in humans, no serotonin-fluorescent cells occurred distal to the point of the entry of the ejaculatory ducts in the male or in the distal one-third of the female urethra. Our previous immunohistochemical study (Iwanaga et al, 1987) recognized numerous serotonin cells dispersed in the human penile urethra. Forsberg et al (1964) demonstrated serotonin-fluorescent cells in the vestibular and lower vaginal epithelia of rabbits, whereas no studies seem available concerning the paraneurons in the vestibule and vagina in other mammals.…”
Section: Introductionmentioning
confidence: 85%
“…Fluorescence histochemistry for monoamines has revealed that serotonin is one of the main contents in the paraneurons in the cat urethra (Owman et al, 1971) and guinea pig urethra and prostate (Haanson et al, 1974). Serotonin-containing paraneurons have been also demonstrated immunohistochemically in the human prostatic urethra and prostate by Fetissof et al (1983) and in the human penile urethra and paraurethral gland by Iwanaga et al (1987).…”
Section: Introductionmentioning
confidence: 99%
“…Populations of specialized cells have been identified in the urethral epithelium of several mammalian species, including humans . Electron microscopy studies identified cells with apical microvilli and basal secretory granules expressing acetylcholine (ACh) and serotonin (5‐HT) .…”
Section: Introductionmentioning
confidence: 99%
“…Populations of specialized cells have been identified in the urethral epithelium of several mammalian species, 8,[12][13][14][15] including humans. 16,17 Electron microscopy studies identified cells with apical microvilli and basal secretory granules expressing acetylcholine (ACh) and serotonin (5-HT). 17,18 ACh was shown to activate muscarinic receptors on subepithelial sensory fibers 18,19 while 5-HT bind 5-HT 2 and 5-HT 3 receptors on urethral sensory fibers leading to the activation of spinal neurons.…”
Section: Introductionmentioning
confidence: 99%
“…The urethral epithelium in human males and females; and in some mammals contains numerous "clear cells" (FEYRTER, 1951(FEYRTER, , 1953, most of which are chromaffin and contain serotonin (DIxON et al, 1973;HAKANSON et al, 1974;IWANAGA et al, 1987). HANYU et al (1987) reported the frequency of the occurrence of the serotonin-immunoreactive cells in the canine urethra of both sexes.…”
Section: Endocrine Cellsmentioning
confidence: 99%